Self Disclosureof Hiv-Positive Women with Counselors at “Bahagia” Medan Social Rehabilitation Center for People with HIV (BRSODH) - Siregar, Ira Nurdewita; Mazdalifah, Mazdalifah; Nurbani, Nurbani (Budapest International Research and Critics University, 2021)
This study aims to describe and analyze how the self-disclosure of women victims of HIV in conducting interpersonal communication with counselors. The research was conducted at the Center for the Social Rehabilitation of People Living with HIV (BRSODHA)